Impact of Order-Set Modifications and Provider Education Following Guideline Updates on Broad-Spectrum Antibiotic Use in Patients Admitted With Community Acquired Pneumonia. (August 2022) - Colmerauer, Jessica L.; Linder, Kristin E.; Dempsey, Casey J.; Kuti, Joseph L.; Nicolau, David P.; Bilinskaya, Anastasia
Purpose: Following updates to the Infectious Diseases Society of America (IDSA) practice guidelines for the Diagnosis and Treatment of Adults with Community-acquired Pneumonia in 2019, Hartford HealthCare implemented changes to the community acquired pneumonia (CAP) order-set in August 2020 to reflect criteria for the prescribing of broad-spectrum antimicrobial therapy. The objective of the study was to evaluate changes in broad-spectrum antibiotic days of therapy (DOT) following these order-set updates with accompanying provider education.Methods: This was a multi-center, quasi-experimental, retrospective study of patients with a diagnosis of CAP from September 1, 2019 to October 31, 2019 (pre-intervention) and September 1, 2020 to October 31, 2020 (post-intervention). Patients were identified using ICD-10 codes (A48.1, J10.00-J18.9) indicating lower respiratory tract infection. Data collected included demographics, labs and vitals, radiographic, microbiological, and antibiotic data. The primary outcome was change in broad-spectrum antibiotic DOT, specifically anti-pseudomonal β-lactams and anti-MRSA antibiotics. Secondary outcomes included guideline-concordance of initial antibiotics, utilization of an order-set to prescribe antibiotics, and length of stay (LOS).Results: A total of 331 and 352 patients were included in the pre- and post-intervention cohorts, respectively. There were no differences in order-set usage (10% vs 11.3%, P  = .642) between the pre- and post-intervention cohort, respectively. The overall duration of broad-spectrum therapy was a median of 2 days (IQR 0-8 days) in the pre-intervention period and 0 days (IQR 0-4 days) in the post-intervention period ( P  < .001). Patients in whom the order-set was used in the post-intervention period were more likely to have guideline-concordant regimens ([36/40] 90% vs [190/312] 60.9%; P  = .003). Hospital LOS was shorter in the post-intervention cohort (4.8 days [2.9-7.2 days] vs 5.3 days [IQR 3.5-8.5 days], P  = .002).Conclusion: Implementation of an updated CAP order-set with accompanying provider education was associated with reduced use of broad-spectrum antibiotics. Opportunities to improve compliance and thus further increase guideline-concordant therapy require investigation.